1993
DOI: 10.1172/jci116705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secretion on intracellular pH regulation in isolated rat bile duct epithelial cells.

Abstract: The effects of secretin on ion transport mechanisms involved in regulation of intracellular pH (pH1) and HCO3 excretion were characterized in bile duct epithelial (BDE) cells isolated from normal rat liver. pHi was measured with 2,7-bis(carboxyethyl)-5(6)-carboxy-fluorescein-acetomethylester (BCECF-AM) using a microfluorimetric method. Basal pHi of BDE was 7.04±0.06 in Hepes and 7.16±0.10 in KRB and was unaffected by secretin (50-200 nM). Recovery rates from an acid load in Hepes or in KRB media (with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
182
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(189 citation statements)
references
References 52 publications
(84 reference statements)
7
182
0
Order By: Relevance
“…This study showed AE2 immunoreactivity restricted to the lumenal surface of the hepatobiliary tree [12]. Such an apical location of AE2 in liver cells is compatible with the reported apical AE activity seemingly involved in the biliary bicarbonate secretion [3,[13][14][15][16]. Although in baseline conditions, expression of alternative transcripts AE2b 1 and AE2b 2 each accounts for about 10% of the full-length AE2a message in the human liver [9], our recent finding that HNF1a may transactivate alternative expression [17] suggests that the physiological significance of alternative AE2 messages might be related to the possibility for liver cells to increase their expression when needed for bicarbonate secretion.…”
supporting
confidence: 85%
“…This study showed AE2 immunoreactivity restricted to the lumenal surface of the hepatobiliary tree [12]. Such an apical location of AE2 in liver cells is compatible with the reported apical AE activity seemingly involved in the biliary bicarbonate secretion [3,[13][14][15][16]. Although in baseline conditions, expression of alternative transcripts AE2b 1 and AE2b 2 each accounts for about 10% of the full-length AE2a message in the human liver [9], our recent finding that HNF1a may transactivate alternative expression [17] suggests that the physiological significance of alternative AE2 messages might be related to the possibility for liver cells to increase their expression when needed for bicarbonate secretion.…”
supporting
confidence: 85%
“…Additional statistical evaluation was also carried out, in which immunostaining data luminal membrane of intrahepatic bile ducts is consistent for each liver structure were categorized as dicotomic qualitative with a possible role for AE2 protein in the generation of canavariables (presence/absence, traces) and analyzed by Fisher's Exact licular and ductular bile through bicarbonate secretion. [6][7][8]14 Test. A final analysis was performed on data from samples having Once the liver specimens included in the present study scores for the three liver structures (a high background sometimes were processed for AE2 immunoperoxidase, stainings were precluded reliable scoring of canaliculi).…”
Section: Group (Normal Liver and Cirrhosis Or Cholestasis Othermentioning
confidence: 99%
“…Normal rats express secretin receptors in the biliary epithelium, 8 and isolated normal rat bile duct units and cholangiocytes both respond to secretin with a cAMPdependent Cl Ϫ efflux and Cl Ϫ /HCO 3 Ϫ exchange activity. 10,11,13,15,16,20 However, in vivo response to secretin could not be shown in normal rats, although these animals effectively respond to the hormone after induction of bile ductular cell hyperplasia. 1,19,[21][22][23][24] In the model of isolated bivascularly perfused normal rat liver (IPRL), 25 secretin (via the hepatic artery) had no influence on the net bile flow, but it did increase biliary concentration of bicarbonate.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Its interaction with a G-protein-coupled receptor selectively localized to the epithelial bile duct cells 8 results in increased intracellular levels of cyclic adenosine monophosphate (cAMP) [cAMP] i 7,9,10 and protein kinase A activation. 11,12 Phosphorylation and opening of a cAMP-dependent Cl Ϫ channel, the cystic fibrosis transmembrane conductance regulator (CFTR), 13 causes Cl Ϫ efflux to the ductular lumen. This appears to stimulate an apical Na ϩ -independent Cl Ϫ /HCO 3 Ϫ anion exchange (AE), 14 with HCO 3 Ϫ efflux and Cl Ϫ influx, that is facilitated by the outside to inside transmembrane gradient of Cl Ϫ at relatively high intracellular HCO 3 Ϫ concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation